Respuesta :

We are given

[tex]cos^{-1}(-x)=-cos^{-1}(x)[/tex]

Firstly, we will simplify left side

and we will check whether it is equal to right side

Left side:

Let's assume y left side expression

[tex]y=cos^{-1}(-x)[/tex]

now, we can take cos on both sides

[tex]cos(y)=cos(cos^{-1}(-x))[/tex]

we can simplify it

[tex]cos(y)=-x[/tex]

Right side:

Let's assume y left side expression

[tex]y=-cos^{-1}(x)[/tex]

Multiply both sides by -1

[tex]-y=cos^{-1}(x)[/tex]

now, we can take cos on both sides

[tex]cos(-y)=cos(cos^{-1}(x))[/tex]

we can simplify it

[tex]cos(-y)=x[/tex]

[tex]cos(y)=x[/tex]

we can see that

both sides cos(y) value is different

so, this is FALSE.........Answer

Answer:

false

Step-by-step explanation:

ACCESS MORE